Հովհաննես Գրիգորյանի բանարվեստի առանձնահատկությունները - Սաիյան, Ռուզաննա
Реалность, человеческие чувства и идеалы, синтезируясь через поэзию,превращаются в художественное слово подчеркивая ответственность поэта за создание человеческих образов в лирике. Новое поколение литераторов в лице Ованеса Григоряна, следуя требованиям современной поэтической системы, обогащает искусство поэзии новым языковым мышлением, при этом главное внимание сосредотачивается на содержании, а не на форме. Reality, human feelings and ideas, synthesizing through poetry, transform into artistic speech, emphasizing the poet‘s responsibility for the creation of human images in lyrics. The new generation of writers in the face of Hovhannes Grigoryan following the demands of modern poetic system, enriches the poetic art with new linguistic thinking wherein the main attention is focused on the content rather than the form.
Keywords: Գրականագիտություն